Density and molar volumes of imidazolium-based ionic liquid mixtures and prediction by the Jouyban-Acree model - Ghani, N.A. (American Institute of Physics Inc., 2016)
The density of imidazolium-based ionic liquid, 1-ethyl-3-methylimidazolium diethylphosphate with sulfolane were measured at atmospheric pressure. The experiments were performed at T= (293 - 343) K over the complete mole fractions. Physical and thermodynamic properties such as molar volumes, V0, and excess molar volumes, VE for this binary mixtures were derived from the experimental density data. The Jouyban-Acree model was exploited to correlate the physicochemical properties (PCPs) of binary mixtures at various mole fractions and temperatures. Â© 2016 Author(s).